Does beauty matter? the role of friends' attractiveness and gender on social attractiveness ratings of individuals on Facebook - Jaschinski, C.; Kommers, Piet (Inderscience Publishers, 2012)
Social network sites have become essential for managing relationships in today's life. Therefore, it is increasingly important for scientist to understand how impressions are formed and connections develop in the virtual world. The current research focuses on the popular social network site Facebook. It seeks to investigate how the attractiveness of Facebook friends affects the impression formation of the profile owner, thereby, including gender effects of target and perceiver. Following this objective, a sample of 78 students took part in the experimental study, rating mocked-up Facebook profiles on the social attractiveness of the owner. Results show that the friends' attractiveness has a direct positive impact on the social attractiveness of the target. The gender of the target and perceiver is not a significant moderator of this relationship. However, a main influence of perceiver's gender could be constituted, implying that male as opposed to female perceivers generally rate strangers more socially attractive on SNSs. Copyright © 2012 Inderscience Enterprises Ltd.